Comparison of empirical indoor propagation models for 4G wireless networks at 2.6 GHz - Zyoud, Al-Hareth; Chebil, Jalel; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul; Zeki, Akram M. (2013)
Indoor path loss models are playing an important role in the design and planning of the 4th generation of the mobile networks. Moreover, it is an important component of system level simulators used to evaluate and test the network performance before it has been established. Many propagation models were proposed for this purpose. Most of these models are for macro and micro cellular networks. Small cell which is known as femtocell has been launched for future networks and it is wildly deployed by the mobile operators around the world. The available propagation models’ accuracy is at question when applied to femtocell design and engineering. This paper attempts to quantify the accuracy of these models by studying and comparing seven different propagation models for four different implementation scenarios at 2.6 GHz and for different separation distances.